Teacher Inquiries Into the Education Journeys of Rangatahi in Alternative Education - Turner-Adams, Hana; Bruce, Judy; Piggot-Irvine, Eileen; Schoone, Adrian (Springer Science and Business Media LLC, 2025)
This action research (AR) project explored critical moments from the education experiences of disenfranchised rangatahi (young people) in Alternative Education (AE). The rangatahi hoped their stories would help teachers, principals, Boards of Trustees, and the Ministry of Education understand their experiences and hear their recommendations for helping vulnerable rangatahi in the future. AE teachers utilised storytelling and arts-based methods that enabled rangatahi to tell their stories. The relational and collaborative nature of AR was crucial to amplify the voices of the rangatahi and their AE teachers. This article shares insights from AE teachers’ inquiries and the AR process. The stories were thematically analysed to understand common schooling experiences. Experiences of microaggressions and microaffirmations, social and cultural spaces, transition and transience, exclusion and alienation, identities and relationships, and pedagogical approaches all impacted rangatahi identity and learning. Recommendations for how teachers and school leaders might adapt their practices to support disenfranchised rangatahi are considered.
Keywords: 3901 Curriculum and Pedagogy; 3902 Education Policy, Sociology and Philosophy; 3903 Education Systems; 3904 Specialist Studies In Education; 39 Education; 4 Quality Education; 13 Education; Education